PENGARUH REWARD, PUNISHMENT, STRES KERJA, DAN KEMAMPUAN KERJA TERHADAP KINERJA KARYAWAN (Studi PT. Kereta Api Indonesia (Persero) Daop 6 Yogyakarta) - Windy Wahyuningtyas; Hastho Joko Nur Utomo; Adi Soeprapto (Jurnal Ilmu Administrasi dan Bisnis, 2018)
This research formulation of the problem is the effect of reward, punishment, work stress and work ability partially and simultaneously on the performance of employees at PT. Kereta Api Indonesia (Persero) Daop 6 Yogyakarta. Descriptive research type with questionnaire as data source. As for the population in this study were all employees of PT.Kereta Api Indonesia (Persero) Daop 6 Yogyakarta totaling 100 employees. The sample in this study were 50 employees, using the Slovin formula with a sampling technique used Probability Sampling, which is a sampling technique that provides equal opportunities for each population to be chosen as a member of the sample and the method used is proportional unstratified random sampling. multiple linear regression. In connection with the results of testing hypotheses, the results of this study indicate the influence of reward, punishment, work stress and work ability both partially and simultaneously. The effect of research results shows a positive direction, which means that a better reward, good punishment, good work stress and good work ability will improve employee performance. Keywords : Reward, Punishment, Job Stress, Work Ability and Employee Performance.